The main objective himmotologii - Волгин, С.Н.; Лашхи, В.Л.; Гришин, Н.Н. (Proceedings of National Aviation University (archive), 2009)
In the articles formulated main tasks of chemmotology and main technologies of decision of majority are indicated from the put tasks.